Double Religious Belonging and Some Commonly Held Ideas about Dialogue and Conversion - Fridlund, Patrik (Mission studies, 2014)
There is often a perceived tension between dialogue on the one hand and conversion on the other hand. This article suggests that this tension may be related to religious conviction and religious belonging being seen as monolithic. A basic idea of this article is that there are suggestive empirical findings and relevant conceptual arguments about double religious belonging in a large sense, which lead to a profound questioning, which undermines established views of religion as comprehensive systems. This has implications for conceptions of dialogue and conversion. It is suggested that a consequence of taking into consideration double religious belonging in a broad sense is that established ideas of religions as comprehensive interpretative schemes are undermined. Instead, one would have to acknowledge the fragmented, partial, and contextual character of religion. Accordingly, interreligious dialogue and conversion must also be understood as diversified, variegated and fragmented phenomena. Dialogue is addressed to specific issues, in precise contexts, regarding particular concerns, and the same could generally be said of the aim to convert others.